A Blinded Comparative Study of Four Commercially Available LEDs and a Laser Light Curing Device - Comisi, John C.; Maucoski, Cristiane; Beller, Jonathan P.; Dennis, Kyle S.; Price, Richard B. (European Journal of Dentistry, 2022)
Objective This study determined the effectiveness of five light-curing units (LCUs; four light-emitting diode [LED] and one laser) used on different settings to photo-activate four conventional resin-based composites (RBCs).Materials and Methods A total of 108 RBC specimens were photo-activated in a white Delrin mold representing a mesial-occlusal-distal (MOD) class II restoration in a molar tooth. The proximal boxes were 5 mm deep, and the mesial-distal length was 12 mm. Immediately after photo-curing, the RBC specimens were immersed in a solvent to remove the uncured materials, after which they were photographed and deidentified. A Research Electronic Data Capture survey was created using these images and sent to respondents who blindly assessed the ability of the various LCUs to photo-cure the MOD restorations.Results There were significant differences in how the five curing lights had cured RBCs. One-way analysis of variance (ANOVA), pairwise t-test, Welch's one-way ANOVA, and Kruskal–Wallis rank test in the blinded survey data showed significant differences between the LED curing lights used for two 10-second cures and the laser curing light used for 1 second, and LED lights at lower settings.Conclusion There was a significant difference in how the curing lights could photo-cure the RBCs used in this study. The laser curing light used for 1 second produced the worst results in all four RBCs.
Keywords: resin-based composites; dental curing lights; LED curing lights; laser curing light